Electroacupuncture ameliorates peptic ulcer disease in association with gastroduodenal microbiota modulation in mice - Li, Xiaoshuang; He, Feiyu; Tuo, Xuan; Qiu, Yuanming; Guo, Jingjing; Wu, Yiming; Meng, Xianjun; Yang, Zongbao (Frontiers in Cellular and Infection Microbiology, 2022)
Peptic ulcer disease (PUD) is a common and frequently occurring disease in clinic. Accumulating evidence suggests that PUD is associated with the gastrointestinal micro dysbiosis. Electroacupuncture (EA), an improved version of acupuncture which can improve the clinical effect by increasing stimulation by delivering appropriate electrical pulses to needles, has been widely used in the treatment of peptic ulcer disease. However, it is unclear about its effect on gastrointestinal microbiota. Therefore, in this study, we evaluated the amelioration effect of EA on gastroduodenal mucosa and the regulation effect of gastroduodenal microbiota in PUD mice. A total of 48 male KM mice were randomly divided into Normal Control group (NC), PUD model group (PUD), Shousanli group (LI10) and Zusanli group (ST36) (n=12). The mice in group LI10 and group ST36 were intervened with EA at LI10 and ST36, respectively, continuing for 7 days. Subsequently, we evaluated the morphological changes of gastric and duodenal mucosa, the contents of serum dopamine (DA), Trefoil Factor (TFF) and Vasoactive Intestinal Peptide (VIP), and analyzed the microbiota of gastric and duodenum by 16S rDNA gene sequencing. The results show that EA at LI10 or ST36 significantly reduced the injury of gastroduodenal mucosa in PUD mice. Compared with PUD model group, the gastric microbial composition of group LI10 and group ST36 tended to that in group NC; the abundance of Firmicutes in stomach decreased and the abundance of Bacteroidetes increased; the abundance of Firmicutes in duodenum decreased. In addition, the microbial diversity and richness of gastric in group LI10 also increased significantly, and the serum DA and TFF in group ST36 increased significantly. Therefore, we suggest that EA could regulate the composition and structure of microbiota in gastric and duodenum, which provides a basis for further understanding the mechanism of PUD treatment from the perspective of intestinal flora.